Rational design of an acidic erythritol (ACER) medium for the enhanced isolation of the environmental pathogen Burkholderia pseudomallei from soil samples - Assig, Karoline; Lichtenegger, Sabine; Bui, Linh N. H.; Mosbacher, Bettina; Vu, Anh T. N.; Erhart, Daniel; Trinh, Trung T.; Steinmetz, Ivo (Frontiers in Microbiology, 2023)
The soil bacterium Burkholderia pseudomallei causes melioidosis, a potentially fatal and greatly underdiagnosed tropical disease. Detection of B. pseudomallei in the environment is important to trace the source of infections, define risk areas for melioidosis and increase the clinical awareness. Although B. pseudomallei polymerase chain reaction (PCR)-based environmental detection provides important information, the culture of the pathogen remains essential but is still a methodological challenge. B. pseudomallei can catabolize erythritol, a metabolic pathway, which is otherwise rarely encountered among bacteria. We recently demonstrated that replacing threonine with erythritol as a single carbon source in the pH-neutral threonine-basal salt solution (TBSS-C50) historically used improved the isolation of B. pseudomallei from rice paddy soils. However, further culture medium parameters for an optimized recovery of B. pseudomallei strains from soils are still ill-defined. We, therefore, aimed to design a new erythritol-based medium by systematically optimizing parameters such as pH, buffer capacity, salt and nutrient composition. A key finding of our study is the enhanced erythritol-based growth of B. pseudomallei under acidic medium conditions. Our experiments with B. pseudomallei strains from different geographical origin led to the development of a phosphate-buffered acidic erythritol (ACER) medium with a pH of 6.3, higher erythritol concentration of 1.2%, supplemented vitamins and nitrate. This highly selective medium composition shortened the lag phase of B. pseudomallei cultures and greatly increased growth densities compared to TBSS-C50 and TBSS-C50-based erythritol medium. The ACER medium led to the highest enrichments of B. pseudomallei as determined from culture supernatants by quantitative PCR in a comparative validation with soil samples from the central part of Vietnam. Consequently, the median recovery of B. pseudomallei colony forming units on Ashdown’s agar from ACER subcultures was 5.4 times higher compared to TBSS-C50-based erythritol medium (p = 0.005) and 30.7 times higher than TBSS-C50 (p < 0.001). In conclusion, our newly developed ACER medium significantly improves the isolation of viable B. pseudomallei from soils and, thereby, has the potential to reduce the rate of false-negative environmental cultures in melioidosis risk areas.